The effect of repetitive exposure to intravenous anesthetic agents on the immunity in mice - Park, Hyun Jun (Int J Med Sci, 2020)
Introduction: This study was designed to assess the effect of repetitive exposure to intravenous anesthetic agents on the immunity in mice. Materials and Methods: The mice were divided into six groups: three intravenous anesthetic agents groups (dexmedetomidine, midazolam and propofol groups), and three corresponding control groups (C(D), C(M), and C(P) groups). The intravenous injections were administered once per day for 5 days. The immunity of mice was checked after the last intravenous injection. Histopathology and immunochemistry of liver and kidneys were evaluated. Cytokine levels in the blood was also checked. vs. evaluated with cytokine levels in the blood. Results: Cluster of differentiation (CD)4(+) T cells were significantly less expressed in dexmedetomidine and propofol groups, compared with the corresponding control groups [34.08 ± 5.63% in the dexmedetomidine group vs. 59.74 ± 8.64% in the C(D) group, p < 0.05; 25.28 ± 7.28% in the propofol group vs. 61.12 ± 2.70% in the C(p) group, p < 0.05]. Apoptosis of CD4(+) T cells was increased significantly in dexmedetomidine and propofol groups, compared with the corresponding control groups. Histopathological findings of liver and kidneys did not show any specific differences of any of three intravenous anesthetic agents groups with their corresponding control groups, although immunohistochemical examination indicated significantly lower expression of Toll-like receptor-4 from liver and kidneys in dexmedetomidine and propofol groups. The cytokine levels were not different between the groups. Conclusion: Repetitive exposure to dexmedetomidine and propofol reduced the expression of CD4(+) T cells but did not induce any significant liver or kidney injuries.